Mechanisms underlining gender differences in Phenylephrine contraction of normoglycaemic and short-term Streptozotocin-induced diabetic WKY rat aorta - Aloysuis, U. I.; Achike, F. I.; Mustafa, Mohd Rais (Elsevier, 2011)
The female gender reduces the risk, but succumbs more to cardiovascular disease. The hypothesis that shortterm 8 weeks) Streptozotocin-induced diabetes could produce greater female thanmale vascular tissue reactivity and themechanistic basiswere explored. Aortic ring responses to Phenylephrine were examined in age- and sex-matched normoglycaemic/diabetic rats. The normoglycaemic male tissue contracted significantly more than the normoglycaemic female and the male/female diabetic tissues. Endothelial-denudation, L-NAME or MB reversed these differences suggesting an EDNO-cGMP dependence. 17Î²-oestradiol exerted relaxant effect on all endothelium-denuded (and normoglycaemic endothelium-intact male) tissues, but not endotheliumintact normoglycaemic female. The greater male tissue contraction is attributable to absent 17Î²-oestradiolmodulated relaxation. Indomethacin blockade of COX attenuatedmale normoglycaemic and female diabetic tissue contraction (both reversed by L-NAME), but augmented diabetic male tissue contraction. These data are consistent with the raised contractile TXA2 and PGE2 in normoglycaemic male and diabetic female tissues, and the relaxant PGI2 in diabetic male (and female). The higher levels of PGI2 in the normoglycaemica and diabetic female perhaps explain their greater relaxant response to Acetylcholine compared to the respective male. In conclusion, there is an endothelium-dependent gender difference in the effect of short term diabetes on vascular tissue reactivity which is COX mediated.